HUBUNGAN POLA ASUH ORANG TUA DENGAN SIBLING RIVALRY PADA ANAK BALITA - Titin Hidayatin; Eleni Kenanga Purbasary; Elsa Ainun Innayah (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2021)
ABSTRACT Introduction: Parenting patterns are one of the factors that affect sibling rivalry in children. Sibling rivalry is a competition or quarrel between siblings (brother or sister). Sibling rivalry occurs because children are afraid of losing the love and attention of both parents. The purpose of this study was to determine the relationship between parenting patterns and the incidence of sibling rivalry in children under five. Methods: The study used a systematic literature review method. Articles are taken from Portal Garuda, Google Scholar, ResearchGate and OneSearch from 2011 to 2021. The procedure for searching and selecting articles uses Preferred Reporting Items for Systematic Reviews & Meta-analysis (PRISMA). Results: Based on 5 articles it is known that there is a relationship between parenting patterns with the incidence of sibling rivalry in children under five, with p value < 0.05. Conclusion: In this study, democratic parenting was chosen by parents to minimize the occurrence of sibling rivalry in children. Suggestions are intended for nurses to be able to apply by providing counseling to parents about the importance of applying appropriate parenting patterns so that sibling rivalry does not occur. Keywords : Parenting pattern, Sibling rivalry.